ANALISIS PERKEMBANGAN DIGITALISASI UMKM DENGAN OPTIMALISASI DIGITAL MARKETING DAN FINANCIAL TECHNOLOGY PADA MASA PANDEMI COVID-19 (Studi Kasus pada Anggota Manajemen Paguyuban Pebisnis Online Kendal) - Fajarwati, Cahyaning (Fakultas Komputer Dan Desain, 2024)
This study aims to provide an explanation of the role of digital marketing and financial technology in helping MSMEs during the Covid-19 pandemic. The research method used is descriptive qualitative, namely by being directly involved in the activities of the object of research and collecting data in the form of images and written or oral words. The research entitled “Analysis of the Development of Digitalization of MSMEs by Optimizing Digital Marketing and Financial Technology during the Covid-19 Pandemic”. Researchers conducted interviews with 7 MSME players, namely: Bumbu Ndeso Online Restaurant, Kedai Mamalia, Mas Faisal Fried Rice, Handalku Abon Ayam, D'Qiya Brownies Chips, Batik Widji, and Lily Homemade. The results of this study indicate that the survival strategy for MSMEs is in the form of e-commerce trading, digital marketing, improving product quality, adding services and establishing and optimizing customer marketing relationships, and utilizing digital payments as a means of financial transactions between producers and consumers.